Securing password transmission for FTMSK webmail system using cryptographic hashing / Prasanna Ramakrisnan ... [et al.] - Ramakrisnan, Prasanna; Md Daud, Md Rosli; Jono, Mohd Nor Hajar Hasrol; Abdul Aziz, Azlan (Universiti Teknologi MARA (UiTM), 2007)
Password is a popular way for authenticating a user to asystem. This method is widely used in many online systems and email systems. This method ensures that only the legitimate users have access to the system. Analysis on the security of the method is important as it is exposed to many kind of attack these days. In this paper, the password vulnerability on the method used by an existing webmail system at FTMSK (Fakulti Teknologi Maklumat dan Sains Kuantitatif) is presented. A simple prototype defence mechanism to modify the existing login page by finding the hashing procedure was developed. We have shown that by implementing cryptographic hashing algorithm, the weakness found in the existing webmail system can be overcome.